Internet of Things: A Survey - Torğul, Belkız; Şağbanşua, Lütfü; Balo, Figen Balo (PLUSBASE AKADEMİ ORGANİZASYON VE DANIŞMANLIK, 2016)
Internet of Things (IoT) is a global infrastructure worldwide which links objects and enables data generation and sharing of this data. IoT is considered as one of the most important areas of future technology and gets attention considerably by researchers and practitioners in recent years. Applications presented by IoT makes possible a large number of developments, but very few can be used currently. With rapid advances in this system technology, successful implementations will continue to emerge to improve the quality of life in many areas. In this study, IoT is examined in general terms and its applications, advantages and disadvantages are reviewed.
Keywords: Engineering; Mühendislik